2002
DOI: 10.1128/jvi.76.23.11837-11844.2002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Molecular and Biological Characteristics of a Modified Live Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) Vaccine (Ingelvac PRRS MLV), the Parent Strain of the Vaccine (ATCC VR2332), ATCC VR2385, and Two Recent Field Isolates of PRRSV

Abstract: The objectives of this study were to compare the molecular and biological characteristics of recent porcine reproductive and respiratory syndrome virus (PRRSV) field isolates to those of a modified live virus (MLV) PRRS vaccine and its parent strain. One hundred seventeen, 4-week-old pigs were randomly assigned to six groups. Group 1 (n ‫؍‬ 20) served as sham-inoculated negative controls, group 2 (n ‫؍‬ 19) was inoculated with Ingelvac PRRS MLV vaccine, group 3 (n ‫؍‬ 20) was inoculated with the parent strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
101
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(111 citation statements)
references
References 30 publications
6
101
1
3
Order By: Relevance
“…This factor and the possibility that the parental wild-type virus and the vaccine itself had low fitness may have prevented the lineage from becoming widespread, as observed for other vaccine-associated lineages. The safety of live attenuated PRRSV vaccines has been questioned since the detection of MLV vaccine revertants which caused productive problems similar to those of wild-type PRRSV (41,52,55). In our analyses, we identified two large vaccine-associated sublineages, with the majority of their sequences being closely related to MLV (sublineage 5.1) and ATP (sublineage 8.9).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…This factor and the possibility that the parental wild-type virus and the vaccine itself had low fitness may have prevented the lineage from becoming widespread, as observed for other vaccine-associated lineages. The safety of live attenuated PRRSV vaccines has been questioned since the detection of MLV vaccine revertants which caused productive problems similar to those of wild-type PRRSV (41,52,55). In our analyses, we identified two large vaccine-associated sublineages, with the majority of their sequences being closely related to MLV (sublineage 5.1) and ATP (sublineage 8.9).…”
Section: Resultsmentioning
confidence: 82%
“…Using restriction fragment length polymorphism (RFLP) typing, it was shown that the prevalence of vaccine strains and vaccine derivatives reached 10% in Quebec (39) and Ͼ33% in Ontario (5). In addition, vaccine derivatives might not share the same attenuated phenotype as their parental types, and reversion to a virulent type has been observed in the field (36,52,55).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PRRSV mainly infects primary porcine alveolar macrophages (PAMs). Previous studies reported that highly pathogenic PRRSV (HP-PRRSV) infection caused severe interstitial pneumonia (44,45), and the protein levels of IL-1b, IL-10, and TNF-a were significantly elevated in HP-PRRSV-infected pigs (46,47). IL-1b level was closely correlated with persistent infection and pathogenesis of PRRSV (48).…”
mentioning
confidence: 84%
“…There are many commercially attenuated or inactivated vaccines for the prevention of PRRS. Research suggests that the attenuated vaccines still might have the ability to mutate to virulent types, and cause vaccine-associated outbreaks (Opriessnig et al, 2002). On the other hand, the immunity provided by these inactivated vaccines is not enough for the animal stock (Nilubol et al, 2004).…”
Section: Introductionmentioning
confidence: 99%